Exploring Fruit Remedies for Ulcer Treatment: An Invitro Analysis - Sireesha Kalva; Salma Sulthana (Asian Journal of Pharmaceutical Research and Development, 2025)
Objective: To compare the anti-ulcer activity of litchi chinensis and withania coagulans fruit extracts using an In-vitro analysis. Design: This was an in-vitro experimental study. It involved comparing the acid-neutralizing capacity of different concentrations of fruit extracts with a standard antacid. Intervention: The interventions were the different concentrations (100mg, 200mg, 500mg, and 1000mg/ml) of the fruit extracts from Litchi chinensis and Withania coagulans. The standard antacid (aluminum hydroxide + magnesium hydroxide at 500mg/ml) also served as an intervention for comparison. Additionally, different formulations (syrup, suspension, and effervescent granules) of the fruit extracts were prepared and tested, with the suspension ultimately being the focus. Main Outcome Measure: The primary outcome measure was the acid neutralizing capacity (ANC) of the fruit extracts at various concentrations. This measured how effectively the extracts could neutralize acid, which is directly related to their potential to treat peptic ulcers. Results: The results showed concentration dependent reduction in acid neutralizing capacity per gm of antacid was found as 157.5, 91.25, 40 and 21.75 for Litchi chinensis and 81, 58, 24 and 14.4 for Withania coagulans. Standard (500 mg/ml) ANC value was found to be 40.1 quite similar concentration of test drug. Whereas, test drug concentration 500 mg/ml was found to neutralize acid more significantly as compared to standard. Conclusion: Different formulations (syrup, suspension and effervescent granules) were prepared using fruit extracts. According to the results suspension has shown better results than other formulations.